Utilization of Information Technology-Based Learning Media to Support Active Learning Activities at State High School 2 Husni Thamrin - Erwin; Joni; Chandra, Wenripin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
In general, high school students view mathematics as a difficult and boring subject. In addition to students, teachers also have difficulty in conveying material for the introduction of majors for lectures. The lack of student interest in learning mathematics is a problem for every high school teacher. This happens if the teacher's ability to use conventional learning methods such as from textbooks and explanations from the teacher only. Therefore, it is necessary to strive in the process of learning mathematics to be more interesting, more interactive and fun. This issue also applies to science materials that require understanding. For this reason, teaching aids are needed that are used to stimulate students' responsiveness in studying material according to their scientific competence. This service aims to apply knowledge and technology by conducting training in making and tutorials on mathematics learning media so that it can increase understanding and attract students' interest in learning and help improve the quality of teacher education and teaching at Husni Thamrin High School.